Comparative study of energy losses related to the ring pack operation in homogeneous charge compression ignition and spark ignition combustion. (15th November 2021) - Koszalka, Grzegorz; Hunicz, Jacek
Abstract: Low-temperature combustion in homogeneous charge compression ignition (HCCI) engine is one of the most promising technologies allowing to meet future emission targets for internal combustion engines. Whereas majority of research is centred on combustion itself, this paper for the first time points out the piston's energy losses induced by friction and blow-by in HCCI engine with negative valve overlap. The energy losses for HCCI and spark ignition (SI) operating modes were compared and thoroughly analysed with the use of the ring pack model. The input data for the simulations came from measurements made on a single-cylinder research engine capable of dual-mode combustion. The energy losses associated with friction of the rings against the cylinder varied from 8.2% of the indicated energy at the lowest load to 2.2% at the highest load tested, and were higher than in the SI mode by approximately 7%. The losses due to the gas leakage through the ring pack in the HCCI mode varied from 8% to 3.3%, respectively, and these losses were about twice as high as in the SI engine. The results demonstrated that energy losses due to blow-by are comparable with the friction losses of the rings, which are usually regarded as the prime source of inefficiency. Highlights: HCCI cycle effect on the ring pack energy losses is demonstrated. Negative valve overlap in HCCI engine highly affects the ring pack performance. The energy losses due to blow-by in an HCCI mode are 100% higher than in an SI mode. The energy losses due to friction of the rings are higher by 7% in an HCCI engine. The energy losses related to blow-by and rings' friction are comparable.